Lenalidomide and dexamethasone for systemic AL amyloidosis following prior treatment with thalidomide or bortezomib regimens. (13th June 2014) - Mahmood, Shameem; Venner, Christopher P.; Sachchithanantham, Sajitha; Lane, Thirusha; Rannigan, Lisa; Foard, Darren; Pinney, Jenny H.; Gibbs, Simon D. J.; Whelan, Carol J.; Lachmann, Helen J.; Gillmore, Julian D.; Hawkins, Philip N.; et al.
Summary The outcomes and responses to treatment remain poorly studied among patients with systemic AL amyloidosis who require further treatment following prior novel agent‐based therapy. We report here treatment with lenalidomide‐dexamethasone in 84 AL amyloidosis patients with relapsed/refractory clonal disease following prior treatment with thalidomide (76%) and/or bortezomib (68%). On an intention‐to‐treat (ITT) basis, the overall haematological response rate was 61%, including 20% complete responses. The median overall survival (OS) has not been reached; 2‐year OS and progression‐free survival (PFS) was 84% and 73%, respectively. Achieving a free light chain (FLC) response was an independent good prognostic factor for OS in multivariate analysis. There was no impact of prior thalidomide or bortezomib therapy on response rate, OS or PFS. 16% achieved an organ response at 6 months, with a marked improvement in organ responses in patients on long term therapy (median duration 11 months) and 55% achieving renal responses by 18 months. Lenalidomide/dexamethasone therapy achieves good haematological responses in patients with AL amyloidosis with relapsed/refractory clonal disease. The rate of renal responses among patients who received prolonged treatment was unexpectedly high, raising the possibility that immunomodulatory effects of lenalidomide therapy might enhance the otherwise slow natural regression of amyloid deposits.